2008
DOI: 10.1007/s11695-008-9727-0
|View full text |Cite
|
Sign up to set email alerts
|

The FTO Obesity Gene. Genotyping and Gene Expression Analysis in Morbidly Obese Patients

Abstract: Our results show: (1) A strong association between rs9939609 SNP of the FTO gene variant and obesity in Spanish morbidly obese adult patients; (2) positive correlations between FTO mRNA and leptin, perilipin, and visfatin gene expressions in subcutaneous adipose tissue; (3) FTO and perilipin gene expressions were positively correlated in visceral fat depot. Overall these results may suggest a role of FTO in the regulation of lipolysis as well as in total body fat rather in fat distribution patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
58
3
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 57 publications
13
58
3
2
Order By: Relevance
“…Nevertheless, in our study, the association of these parameters was independent of body weight. In accord with other study (38), no association between leptin levels and rs9939609 genotypes were detected. In the other hand, Zimmerman et al (23) reported an association between circulating leptin levels and FTO variant, but the effect was accounted for by BMI and that the FTO A-allele tended to lower IL-6 levels.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, in our study, the association of these parameters was independent of body weight. In accord with other study (38), no association between leptin levels and rs9939609 genotypes were detected. In the other hand, Zimmerman et al (23) reported an association between circulating leptin levels and FTO variant, but the effect was accounted for by BMI and that the FTO A-allele tended to lower IL-6 levels.…”
Section: Discussionsupporting
confidence: 89%
“…To date, only a few studies have examined FTO gene expression in paired OAT and SAT and discordant results were reported. Some studies found no site-specific difference (20)(21)(22)33), while another study found a threefold higher FTO expression in SAT compared to visceral adipose tissue (16). The discrepancy of our results with these studies is difficult to interpret, but it is worth noting that our population included women exclusively, and covered the lean to moderately obese range while other studies reporting no difference were performed mostly in severely obese patients of both sexes.…”
Section: Figure 4 Effect Of Fto Silencing On 3t3-l1 Differentiation contrasting
confidence: 91%
“…However, the function of FTO and its role in human obesity and T2D remains to be defined. In particular, the association of FTO expression in adipose tissue with fat depot and with obesity still remains controversial in humans (16,(20)(21)(22)33). In addition, very few studies have investigated the relationship between FTO expression in adipose tissue and insulin sensitivity (18,21).…”
Section: Discussionmentioning
confidence: 99%
“…1 A genome-wide search for obesity and type 2 diabetessusceptibility genes identified several variants in the fat mass-and obesity-associated (FTO) gene region on chromosome 16q12.2, which were strongly associated with obesityrelated traits and increased the risk for this disease. [2][3][4][5][6][7] The human FTO is widely expressed in both fetal and adult tissues, including mesenteric fat, pancreas, liver and adipose tissue, with the highest concentration found in the brain, specifically in the hypothalamus. 2,8 Obese subjects show increased levels of subcutaneous adipose tissue FTO mRNA compared with non-obese subjects.…”
Section: Introductionmentioning
confidence: 99%